Economic backwardness in political perspective - Acemoglu, Daron 1967-; Robinson, James Alan 1960- (NBER working paper series, 2002)
We construct a simple model where political elites may block technological and institutional development, because of a 'political replacement effect'. Innovations often erode elites' incumbency advantage, increasing the likelihood that they will be replaced. Fearing replacement, political elites are unwilling to initiate change, and may even block economic development. We show that elites are unlikely to block development when there is a high degree of political competition, or when they are highly entrenched. It is only when political competition is limited and also their power is threatened that elites will block development. We also show that such blocking is more likely to arise when political stakes are higher, and that external threats may reduce the incentives to block. We argue that this model provides an interpretation for why Britain, Germany and the U.S. industrialized during the nineteenth century, while the landed aristocracy in Russia and Austria-Hungary blocked development.